Prevalence and associated factors of safe and improved infant and young children stool disposal in Ethiopia: evidence from demographic and health survey - Biniyam Sahiledengle (BMC, 2019)
Abstract Background Infant and young children stools are often considered innocuous, and are not disposed of safely despite having a higher pathogen load than adult feces. In Ethiopia, sanitary management of young children's stool is often overlooked and transmission of fecal-oral diseases is still a significant health burden. The study, therefore, describes the prevalence and associated factors of safe and improved child stool disposal. Methods Data from the fourth round of the Ethiopian Health and Demographic Survey (EDHS) conducted in 2016 was used for this analysis. Descriptive statistics were computed. Bivariate and multivariable logistic regression analyses were performed to identify factors associated with safe and improved child stool disposal. Results The prevalence of safe and improved child stool disposal in Ethiopia was 36.9% (95%CI: 33.4-40.5%) and 5.3% (95%CI: 4.3-6.5%) respectively. There was regional variation in the prevalence of safe and improved child stool disposal. The odds of safe stool disposal among households with richest wealth index had 4.54 (AOR: 4.54; 95%CI: 2.89-7.12), richer 3.64 (AOR: 3.64; 95%CI: 2.46-5.38), middle 3.26 (AOR: 2.26; 95%CI: 2.27-4.68), and poorer 1.93 (AOR: 1.93; 95%CI: 1.39-2.68) times higher odds of practicing safe child stool disposal than households with poorest wealth index. Similarly, households found in richest, richer, middle, and poorer wealth index had also (AOR: 20.23; 95%CI: 8.59-47.66), (AOR: 12.53; 95%CI: 5.59-28.10) (AOR: 4.91; 95%CI: 1.92-12.55), and (AOR: 4.50; 95%CI: 2.06-9.84) higher odds of practicing improved child stool disposal than households from poorest wealth index respectively. The odds of safe child stool disposal were higher among households whose children age between 6 and 11 months (AOR: 1.57; 95%CI: 1.17-2.09), 12-17 months (AOR: 1.39; 95%CI: 1.00-1.95), and 18-23 months (AOR: 1.43; 95%CI: 1.03-1.99) than households whose children age between 0 and 5 months. The odds of safe child stool disposal were 1.31 (AOR: 1.31; 95%CI: 1.00-1.72) and 1.44 (AOR: 1.44; 95%CI: 1.04-2.01) times higher among mothers whose age between 25 and 34 and greater than 34 years compared to mothers whose age between 15 and 24 years, respectively. In addition, children's stools are more likely to be disposed of safely in urban households than in rural households (AOR: 3.12; 95%CI: 1.86-5.22). The present study also revealed households with access to improved sanitation facilities fail to use them for disposal of child stool (AOR: 0.99; 95% CI: 0.67-1.45). Conclusions The prevalence of safe and improved child stool disposal in Ethiopia was found to be very low. Household socio-demographic and economic determinate were the key factors associated with child stool disposal. Appropriate strategic interventions to ensure safe and improved child stool disposal in Ethiopia is necessary. In addition, integrating child stool management into the existing sanitation interventions programs should be strongly recommended.